Developing an E-Comic for History Education: A Digital Learning Intervention on the Samudra Pasai Kingdom - Johan Setiawan; Viona Corrnellya Putri Kodestama; Moh. Imron Rosidi; Muhammad Hanif (Ta'dib, 2025)
This study aims to develop e-comic-based history learning media on the topic of the Samudra Pasai Kingdom for senior high school students. The urgency of this research lies in the fact that history learning in many schools is still dominated by conventional methods, which often make students less motivated and hinder their ability to engage meaningfully with historical narratives. To address this issue, the Research and Development (R&D) method was employed, adopting the Sugiyono development model that consists of needs analysis, product design, expert validation, and revision. Data were collected through interviews, questionnaires, and classroom observations involving history teachers and tenth-grade students at SMA Muhammadiyah 1 Pekalongan. The findings indicate that: (1) existing learning media at the school remain limited in variety and innovation, resulting in students’ difficulties in understanding historical material; (2) the developed e-comics were designed to provide a more engaging summary of content, enriched with relevant illustrations and integrated media elements; and (3) validations by material and media experts confirmed that the e-comics are appropriate and feasible for use in history learning. The study concludes that e-comic media have significant potential to enhance students’ motivation, participation, and comprehension of history lessons, particularly concerning the Samudra Pasai Kingdom, while also fostering the integration of digital technology into history education in schools.